Experimental Investigation on Shear Resistance Behaviour of RC Precracked and Non-Precracked T-Beams using Discrete CFRP Strips - Jayaprakash, J.; Abdul Samad, A.A.; Ashrabov, A.A.; Choong, K.K. (International Journal of Integrated Engineering, 2009)
The exploitation of Fibre Reinforced Polymer (FRP) composites as external reinforcement is an evergreen technique for improving the structural performance of the existing Reinforced Concrete (RC) structures. This paper presents a experimental investigation on shear strengthening capacity and modes of failure of precracked and non-precracked RC beams bonded externally with bi-directional Carbon Fibre Reinforced Polymer (CFRP) fabric strips. Twelve RC T- beams were fabricated with different internal longitudinal and shear reinforcements. These beams were subjected to two types of loading; namely three point and four point bending systems. The beams were classified into three categories namely control, precracked-repaired, and initially strengthened (i.e. non-precracked) beams. Prior to the application of CFRP shear reinforcement, the precracked-repaired beams were partially loaded to develop shear cracks along the shear spans, whereas the initially strengthened beams were strengthened with CFRP reinforcement without the application of any preloading. The overall increase in shear enhancement of the precracked-repaired and initially strengthened beams ranged between 13% and 61% greater over their control beams. It was found that the application of CFRP strips in the precracked-repaired beams attained better performance as compared to the initially strengthened beams.